A rare case of primary EBV infection causing acute acalculous cholecystitis - Sonia Shah; Sangeeta Schroeder (Elsevier, 2015)
Primary Epstein-Barr Virus (EBV) infection in children is common and frequently asymptomatic. While symptomatic patients typically present with features of infectious mononucleosis, a rare complication of primary EBV is acute acalculous cholecystitis. A 6 year old previously healthy boy presented with 6 days of low-grade fevers, non-bloody non-bilious vomiting, and periumbilical pain. Based on clinical, laboratory, and radiographic evidence, the patient was diagnosed with acute acalculous cholecystitis due to a primary EBV infection. The patient improved with supportive therapy and remained asymptomatic at follow-up. Overall, clinicians should consider EBV infection in the setting of multi-organ disease and blood dyscrasia. Furthermore, while the pathogenesis of EBV cholecystitis is still unclear, it is important to note that these patients may improve with supportive treatment and do not require surgical intervention.